Dietary Flavonoids and Human Cognition: A Meta‐Analysis. Issue 21 (7th April 2022) - Cheng, Nancy; Bell, Lynne; Lamport, Daniel J.; Williams, Claire M.
Abstract: Improving cognition is important in all age groups, from performance in school examinations to prevention of cognitive decline in later life. Dietary polyphenols, in particular flavonoids, have been examined for their benefits to cognitive outcomes. This meta‐analysis evaluates the effects of dietary flavonoids on cognition across the lifespan. In January 2020 databases were searched for randomized controlled trials investigating flavonoid effects on human cognition. Eighty studies, comprising 5519 participants, were included in the final meta‐analysis. The global analysis indicates dietary flavonoids induced significant benefit to cognitive performance ( g = 0.148, p < 0.001), with subgroup analyses revealing that cocoa ( g = 0.224, p = 0.036), ginkgo ( g = 0.187, p ≤ 0.001), and berries ( g = 0.149, p = 0.009) yielded the most notable improvements. Significant benefits were observed from chronic studies, in middle‐aged and older adults, and with low and medium doses. The domains of long‐term memory, processing speed, and mood showed sensitivity to flavonoid intervention. This meta‐analysis provides evidence for the positive effects of flavonoids on cognition and highlights several moderating factors. Flavonoid‐based dietary interventions therefore potentially offer a highly accessible, safe, and cost‐effective treatment to help tackle the burden of cognitive decline. Abstract : A meta‐analysis reveals positive effects of flavonoids on cognition across the human lifespan. These effects are influenced by flavonoid source, dose, supplementation duration, cognitive health, and age. Benefits are observed following berries, cocoa, and ginkgo supplementation and with low and medium doses. While positive effects are shown in middle‐ aged and older adults, these are more pronounced in cognitively unhealthy groups.